Asuhan Kebidanan pada Ibu Hamil dengan Anemia melalui Pemberian Pisang Ambon di Puskesmas Sungai Andai Banjarmasin - Karina Dewi; Nita Hestiyana; Susanti Suhartati; Lisda Handayani (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Anemia in pregnant women remains a global health problem with a high prevalence, including 63.5% in Indonesia. In South Kalimantan in 2023, the prevalence was recorded at 41% in Banjar Regency and 26% in Banjarmasin City, with cases at Sungai Andai Health Center increasing from 46% (2022) to 54% (2023). Iron deficiency poses risks to both mother and fetus, therefore alternative nutritional sources are needed. Ambon banana can be an option as it contains iron and folic acid, is easy to consume, and is affordable. To provide midwifery care for anemic pregnant women by providing Ambon bananas at Sungai Andai Community Health Center, BanjarmasinA descriptive study with samples of pregnant women with anemia at Sungai Andai Health Center. Data were collected through interviews, observation, physical examination, and hemoglobin tests. The intervention was carried out by administering 100 grams of Ambon bananas twice daily for 14 days.Mrs. R, 11 weeks pregnant, complained of nausea, weakness, and dizziness that interfered with her daily activities. The examination showed mild anemia with an Hb level of 10.8 g/dl.The administration of Ambon bananas for 2 weeks was effective in increasing Hb levels in pregnant women with anemia by 2.1 g/dL and can serve as an alternative source of additional nutrition that is easily accessible and affordable